Evidence of Soldering Technology on Pre‐Columbian Gold Pendants from Western and North‐Western Colombia. (10th January 2017) - Harrison, A.; Howe, E.
Abstract : Microscopic examination and analysis (metallography, X‐radiography, SEM–EDS, pXRF and μ‐XRF) of a group of stylistically linked gold alloy pendants from western and north‐western Colombia confirms the use of a highly unusual manufacturing technique for the region. While the Darién pendants were made using lost‐wax casting by a diverse group of cultures from southern Colombia through Costa Rica, only one subset of pendants produced in the Gran‐Zenú region (the Caribbean lowlands of northern Colombia) and the Chocó region (the Pacific area of western Colombia) in the Early Period (ad 0–900) was found to be manufactured by hammering of gold sheet and fine wires followed by hard soldering of components to produce true filigree. Similarities in features between the stylistically related cast and hammered pendants suggest that the hammered pendants may have served as a prototype for the cast versions. Other possible instances of hard soldering in the region are also presented.